2009
DOI: 10.1210/me.2008-0454
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Progesterone Receptor Functional Domains in Stable Cell Lines Delineates Sets of Genes Regulated by Different Mechanisms

Abstract: Steroid hormone receptors act directly in the nucleus on the chromatin organization and transcriptional activity of several promoters. Furthermore, they have an indirect effect on cytoplasmic signal transduction pathways, including MAPK, impacting ultimately on gene expression. We are interested in distinguishing between the two modes of action of progesterone receptor (PR) on the control of gene expression and cell proliferation. For this, we have stably expressed, in PR-negative breast cancer cells, tagged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 42 publications
4
37
0
Order By: Relevance
“…FGF2 activated both PRE-and GAS-luc. When we moved to a more physiologic setting, CCND1 and MYC mRNA were also increased by both ligands as well as all the MPA/STAT5-regulated proteins studied (30,45). The FGFR inhibitor and 2 different antiprogestins not only inhibited cell proliferation induced by MPA or FGF2, respectively, but also inhibited the induction of luciferase expression, mRNA, and protein expression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…FGF2 activated both PRE-and GAS-luc. When we moved to a more physiologic setting, CCND1 and MYC mRNA were also increased by both ligands as well as all the MPA/STAT5-regulated proteins studied (30,45). The FGFR inhibitor and 2 different antiprogestins not only inhibited cell proliferation induced by MPA or FGF2, respectively, but also inhibited the induction of luciferase expression, mRNA, and protein expression.…”
Section: Discussionmentioning
confidence: 95%
“…Discussion, page 3728, second column, last paragraph: When we moved to a more physiologic setting, CCND1 and MYC mRNA were also increased by both ligands as well as all the MPA/STAT5-regulated proteins studied (45,29 To request permission to re-use all or part of this article, use this link…”
Section: Correctionmentioning
confidence: 99%
“…7C -iii-). The regulation of human CCND1 by progestins may be more complicated, as no canonical PRE sites have been described in its promoter and accordingly, it has been suggested that PR regulates CCND1 expression by nongenomic mechanisms (7,9,34). The 2 models of cytoplasmic signaling pathways activated by Pg are shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7C -v-). However, it has been recently shown that PR may have genomic effects at the CCND1 promoter (34,44), even as a coactivator of STAT3 (26; Fig. 7C -iv-).…”
Section: Discussionmentioning
confidence: 99%
“…First, we measured the effect of BRCA1 on PR levels in the cell line FLAG-PRB-T47DYV [a PR-negative clonal derivative cell line from T47D engineered to express a FLAG-tagged form of PRB (20)]. Cell extracts were prepared from control and from cells transduced to overexpress BRCA1 (AdBRCA1; Fig.…”
Section: Brca1 Regulates the Downregulation Of Prmentioning
confidence: 99%